(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article provides information about the artist’s artistic world and his artistic portrait in the lyrics. The aesthetic impact of the artistic portrait is shown. The theoretical ideas are based on the poems of the poetess Zulfiya.